ANALISIS PERILAKU WISATAWAN DALAM MEMBUANG SAMPAH DI KAWASAN BENTENG SOMBA OPU MAKASSAR - Akhmad Saifi; Heri Susanto; Fitri Mardiani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The behavior of tourists in throwing rubbish in the Sombs Opu fort area is the cause of the decline in the aesthetic value of the environment. This research aims to analyze tourist behavior in throwing away rubbish in the Somba Opu fort area with the hope that tourists can better understand the problem of environmental pollution. This research uses a description method carried out through a survey with a data collection method using a questionnaire. The research location is the Somba Opu fort area with the research sample being tourists from the Somba Opu fort, Barombong District, Gowa Regency, Makassar City, totaling 30 people. Then the research data was analyzed to determine the behavior of tourists throwing rubbish in the Somba Opu fort area with the research results from highest to lowest being an attitude indicator of 87%, a knowledge indicator of 80%, and an infrastructure indicator of 63%. Research results show that this is due to tourists' lack of awareness of the risks posed by waste that is disposed of inappropriately. The high level of tourist knowledge cannot be a benchmark for awareness of maintaining the beauty of the Somba Opu fort area.